PERANAN KOMPETENSI KOMUNIKASI DALAM MENINGKATKAN PROFESIONALISME DOSEN MENYONGSONG GERAKAN MERDEKA BELAJAR - Wijayanti, Astuti; Sila, I Made (Jurnal Kajian Ilmu Komunikasi, 2021)
The competency of lecturer is the combination of holistic personal, scientific, technological, social, and spiritual competence which construct a standard competency of a lecturer which covers mastery of material, understanding of students in educated lesson, personal, and professional development. There are four competencies of lecturer in general, namely: pedagogical, professional, social, and personal competencies. Those competencies deductively require the lecturer to be competence in science and technology as well as good communication skill.This study aimed specifically at analyzing the importance of communication competency for lecturer in freedom to learn era. The lecturer is expected to create harmonious relationship to the students in guiding students’ development based on the era. The problem studied was regarding the role of communication competency to improve professionalism of lecturer in freedom to learn era.The inventoried problem was studied using structural-functional and constructive theories. The lecturer has communicative competency in freedom to learn era to run effective teaching and learning activity. The lecturer is not merely a teacher and educator but also as facilitator which guides students to reveal their identity and develop independently as according to the era for getting ready to future